Representasi Tanggung Jawab Generasi Sandwich dalam Film “Home Sweet Loan” Karya Sabrina Rochelle Kalangie 2024 - Tara Herianti; Titin Setiawati; Andys Tiara (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Research critically investigates how the responsibilities of the sandwich generation are represented in the film Home Sweet Loan (2024), by Sabrina Rochelle Kalangie. The sandwich generation refers to individuals burdened with caring for aging parents while also supporting children or siblings. This research applies a qualitative approach using content analysis, grounded in McQuail’s media content theory and the concept of responsibility by Burhanudin and the Ministry of Education and Culture. The analysis of ten key scenes reveals that the character Kaluna embodies layered responsibilities financial, domestic, emotional, and relational. The film not only reflects the realities of the sandwich generation in urban Indonesian society but also critiques unequal familial expectations. Thus, Home Sweet Loan functions as a medium of representation and social critique, addressing the structural pressures faced by today’s younger generation.